2022
DOI: 10.3390/molecules27113633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Open Chain and Cyclic Structure of Peptidomimetics on Antibacterial Activity in E. coli Strains

Abstract: An efficient method for the synthesis of functionalized peptidomimetics via multicomponent Ugi reaction has been developed. The application of trifluoroethanol (TFE) as a reaction medium provided desired products with good yields. Further, using the developed cyclisation reaction, the obtained peptidomimetics were transformed into the cyclic analogues (diketopiperazines, DKPs). The goal of the performed studies was to revised and compare whether the structure of the obtained structurally flexible acyclic pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 39 publications
8
20
0
Order By: Relevance
“…All selected analyzed β-phosphonate derivatives ( Figure 3 ) with different substituents located at the phenyl ring are responsible for the change of the topology of bacterial DNA. After digestion with Fpg, approximately 3.5% of oxidative damage was identified, which very strongly indicates oxidative damage in bacterial DNA, similar to the previous observations [ 71 , 72 , 73 , 74 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…All selected analyzed β-phosphonate derivatives ( Figure 3 ) with different substituents located at the phenyl ring are responsible for the change of the topology of bacterial DNA. After digestion with Fpg, approximately 3.5% of oxidative damage was identified, which very strongly indicates oxidative damage in bacterial DNA, similar to the previous observations [ 71 , 72 , 73 , 74 ].…”
Section: Resultssupporting
confidence: 90%
“…All selected analyzed derivatives of β-phosphonate derivatives, including various types of alkoxy groups, substituents located at aromatic rings, and the length of the alkyl chain, can strongly change the bacterial DNA topology. After Fpg digestion, approximately 3.5% of the oxidative damage was identified, which, similar to previous observations, indicates very strong oxidative damage in bacterial DNA [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Different types of alkoxy groups, substituents located on the aromatic ring and the length of the alkyl chain, may determine the toxicity of the analyzed E. coli strains, including, in particular, R4, as evidenced by the obtained MIC, MBC, and MTT values.…”
Section: Methodssupporting
confidence: 89%
“…Based on the observed results in the MIC and MBC tests, it was found that the analyzed compounds significantly influenced the defragmentation of the membrane and the structure of the cell wall of bacteria containing LPS of various lengths [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 28 , 29 , 30 , 31 ], causing oxidative stress to damage and modification of bacterial DNA. This was further confirmed by the digestion with a specific enzyme Fpg of modified bacterial DNA (Labjot, New England Biolabs, UK), recognizing oxidized guanine and adenine.…”
Section: Resultsmentioning
confidence: 99%
“…This was further confirmed by the digestion with a specific enzyme Fpg of modified bacterial DNA (Labjot, New England Biolabs, UK), recognizing oxidized guanine and adenine. The obtained values of oxidative damage, after digestion with the Fpg protein in the bacterial DNA, were compared with the modifications of the bacterial DNA after treatment with antibiotics such as ciprofloxacin, bleomycin and cloxacillin [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 28 , 29 , 30 , 31 ] ( Figure 6 ). The presented research shows that diethyl benzylphosphonate derivatives can be used in the future as typical “substitutes” for new drugs in relation to the antibiotics used in hospital infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation